Some legal issues in law enforcement machinery of the judiciary - Філик, Наталія Володимирівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2010)
In this article an author analyzes some issues of enabling legislation legal technique of judicial authorities. There the approaches of understanding of legal technique and its types are researched and the legal technique of judicialacts as a separate type of legal technique of law enforcement authorities is separated. An author examines the legal conflicts which arise during making judgments and offers the ways of removal of gaps by using legal technique elements.